Perception of the Medical Speech-Language Pathologist Clinical Educator on Graduate Speech-Language Pathology Student Readiness for Clinical Placement in Medical Settings: An Exploration. - Perez, Christina; St. Clair, Jennifer; Maring, Joyce (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: Securing sufficient clinical placements, especially in medical settings, remains a challenge for many communication sciences and disorders graduate programs. Medical speech-language pathologist (SLP) clinical educators (CEs) consider factors such as student competency, clinical readiness, and professionalism when deciding whether to supervise students in medical environments. This preliminary study investigates medical SLP CEs' perceptions on key facilitators of and barriers to preparing graduate speech-language pathology students for clinical placement in medical settings. Method: Seventy-six medical SLP CEs from across the United States participated in this anonymous survey. The survey focused on three key domains: academic and clinical preparation, professionalism, and clinical readiness. Descriptive statistics were used to analyze quantitative responses, whereas thematic content analysis was applied to open-text responses. Results: Approximately half of the respondents agreed that students demonstrated foundational knowledge and clinical applications in aphasia and speech sound production. However, fewer respondents agreed that students were prepared for dysphagia, voice disorders, cognitive-communication disorders, and auditory rehabilitation. Although most CEs reported that students showed professionalism and clinical readiness, many highlighted ongoing challenges in documentation, self-awareness, and respect for the CE's role. The free-text themes identified were educational strategies, academic-clinical integration, mentorship, and reflective practice and self-development. Conclusions: Preliminary findings suggest that graduate speech-language pathology student readiness for medical placements may be influenced by theoretical preparation, structured observation, clear expectations, and mentorship. Addressing curricular gaps in dysphagia and voice could enhance confidence, professionalism, and clinical competence.